Fetus-in-fetu presenting as a cryptorchid testis and abdominal mass: A report of a case and review of the literature - A. Landmann; J.L. Calisto; M. Reyes-Múgica; D. Thomas; M.M. Malek (Elsevier, 2016)
Fetus-in-fetu is a rare congenital tumor containing fetal tissue with an unclear etiology, but some believe it to arise from a parasitic monozygotic twin within the host twin. We present the case of a 3-week old term neonate found to have an abdominal mass and undescended right testicle. At laparotomy, a large, circumscribed mass was present in the right upper quadrant. It was found to be associated with the vas deferens and gonadal vessels, appearing to be closely associated with the right-sided cryptorchid testis. Pathology revealed an intratesticular fetus-in-fetu. Fetus-in-fetu is a rare condition where a well-developed mass believed to arise from a monozygotic, parasitic twin, is found within its sibling. First reported by Dr. Meckel in 1800, this is thought to occur in 1 in 500,000 live births with less than 100 cases reported in the literature. Fetus-in-fetu is differentiated from mature teratoma by the presence of an axial skeleton with metameric segmentation and well-differentiated tissues. FIF is a benign disease, however surgical excision continues to be the treatment of choice, in order to confirm diagnosis by pathology and to exclude malignant teratoma. Fetus-in-fetu is a rare of congenital lesion that can present as an abdominal mass. Due to the high prevalence of retroperitoneal location, a FIF should remain on the differential for an infant with an abdominal mass and ipsilateral cryptorchid testis.